2002
DOI: 10.4049/jimmunol.168.3.1315
|View full text |Cite
|
Sign up to set email alerts
|

YersiniaenterocoliticaEvasion of the Host Innate Immune Response by V Antigen-Induced IL-10 Production of Macrophages Is Abrogated in IL-10-Deficient Mice

Abstract: The virulence-associated V Ag (LcrV) of pathogenic Yersinia species is part of the translocation apparatus, required to deliver antihost effector proteins (Yersinia outer proteins) into host cells. An orthologous protein (denoted as PcrV) has also been identified in the ExoS regulon of Pseudomonas aeruginosa. Additionally, it is known that LcrV is released by yersiniae into the environment and that LcrV causes an immunosuppressive effect when injected into mice. In this study, we demonstrate for the first time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
109
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 51 publications
(23 reference statements)
7
109
0
Order By: Relevance
“…IL-10 is a cytokine with broad antiinflammatory properties that results from its ability to inhibit functions of both macrophages and dendritic cells, including secretion of their proinflammatory cytokines [24] and NO production [25]. Sing et al [26] reported that low calcium response V (LcrV) or antigen V, a secreted antihost protein with strong immunomodulatory effects that is associated Yersinia virulence, inhibits zymosan-induced production of TNF-a by inducing IL-10. The increase of IL-10 production, in the early period of infection, was consistent with the observed decrease of proinflammatory cytokines and NO production in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a cytokine with broad antiinflammatory properties that results from its ability to inhibit functions of both macrophages and dendritic cells, including secretion of their proinflammatory cytokines [24] and NO production [25]. Sing et al [26] reported that low calcium response V (LcrV) or antigen V, a secreted antihost protein with strong immunomodulatory effects that is associated Yersinia virulence, inhibits zymosan-induced production of TNF-a by inducing IL-10. The increase of IL-10 production, in the early period of infection, was consistent with the observed decrease of proinflammatory cytokines and NO production in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pretreatment of wildtype peritoneal macrophages with recombinant LcrV (rLcrV) inhibited zymosan induced TNF-production. The anti-inflammatory effect of macrophages was found to be IL-10 dependent because it could be reversed by neutralizing antibodies specific to IL-10.There was no effect of neutralizing antibodies against IL-4 or TGF-, two other cytokines known to inhibit inflammatory responses of macrophages (Sing et al, 2002). The cell receptors responsible for LcrV-induced IL-10 production were identified as CD14 and TLR2 (Sing et al, 2002).…”
Section: Immunology Of Y Pestismentioning
confidence: 89%
“…IL-10 secretion in response to rLcrV was abrogated in CD14-and TLR2-deficient m a cr o ph ag e s . Fu r th erm o r e , th e T L R 2 s t imu l a t ing r eg i on o f L c r V m app e d t o a s h o rt Nterminal 19 amino acid sequence (Sing et al, 2002). CD14 / TLR2 mediated production of IL-10 by LcrV was further established by the observation that TLR2-deficient mice were more resistant to Y. enterocolitica infection than their wild-type parents (Sing et al, 2002).…”
Section: Immunology Of Y Pestismentioning
confidence: 98%
See 2 more Smart Citations